The roots of my hair : a graphic novel - Lubie, Lou (Helvetiq, 2026)
A bold, funny, and insightful graphic novel about hair, heritage, and identity. The Roots of My Hair follows the coming-of-age journey of Rose, a mixed-race woman from Reunion Island who struggles to love her kinky hair in a world that tells her to tame it. As she moves to mainland France to study and later to work--experimenting with different hair-straightening techniques, visiting beauty salons, and adopting social camouflage--Rose explores her Black identity by questioning the deeper issues behind her hair: race, beauty standards, colonialism, and belonging. With humor, honesty, and expressive illustrations, Lou Lubie's new graphic novel blends original research and fiction, not only to reveal what lies beneath the hair-care industry but also to speak to anyone who has ever felt pressure to fit in. It is a powerful reminder that identity starts at the roots.